O CRAS como estratégia para efetivação da proteção social básica na esfera municipal: desafios, tensões e direções - Araujo, Therese Abdel Messih (2009)
This research analyses the process of reorganization of services, programs and projects of the politics of social assistance, from the basic social protection's logic and from new conceptual matrixes established in Brazilian's National Politics of Social Assistance approved in 2004. Considering the Social Assistance Reference Centers - CRAS's installation as an strategy for accomplishing the basic social protection of social assistance, this research aims to demonstrate how the concept of basic social protection have been incorporated as a new paradigm, in contraposition at the emergency pattern and the discretion historically present on the social assistance trajectory in Brazil. The spacial dimension of this study is circumscribed on the cities of Louveira and Vinhedo, which are part of the Campinas Administration Region, based on the relevance of the municipal sphere on the institutionalization of a public social protection net accessed as citizenship right, and has the objective of capturing the form that the social assistance politics express itself and materializes on these cities, aiming to unmask the roots on the territory, the current infra-structure conditions, the political support on the county management, the creation of democratic forums and the evolvement of the social assistants as the agents which makes happen the implantation of the SUAS. Preliminarly was made documental research with the County Councils of Louveira and Vinhedo, what made the historically reconstruction of the institutionalization of the social assistance politics on the cities possible. The field research was developed with the county managers of social assistance, the basic social protection coordinators, CRAS workers and cities social assistance councils, chosen for contemplate the technical and political directive configuration that is happening with the CRAS implantation, based on the vision of distinct public agents related with that process. The results we got along the investigation reveal us that the apprehension of the basic social protection, in its conceptual dimension, presents aspects that approaches itself with the PNAS/04's proposal but that still faces theory-methodological fragilities as well as technical and operational, besides resistances for the overcoming of the emergency and subsidiary mark that is following the social assistance trajectory, making it difficult the delimitation of its preventive perspective. Although, the implantation of the CRAS as public-state units show advances to a social assistance consolidation as a public politic. However, it s important to be careful not to be reduced to regional social support units, reproducing conservative and tutoring tendencies, that end for not making possible the access to the social-assistance rights on the Social Assistance Unique System SUAS s ground